2021
DOI: 10.3390/met11081288
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution Models for Metallurgical Coke Grinding Products

Abstract: Six different particle size distribution (Gates–Gaudin–Schuhmann (GGS), Rosin–Rammler (RR), Lognormal, Normal, Gamma, and Swebrec) models were compared under different metallurgical coke grinding conditions (ball size and grinding time). Adjusted R2, Akaike information criterion (AIC), and the root mean of square error (RMSE) were employed as comparison criteria. Swebrec and RR presented superior comparison criteria with the higher goodness-of-fit and the lower AIC and RMSE, containing the minimum variance val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The experiments conducted in a wet stirred media mill showed that increasing the grinding time decreases the median particle size of pumice with a simultaneous increase in the unit energy demand (Table 2 and Figure 2). A similar observation for the stirred ball mill was presented in the author's previous study for limestone [24] and other types of mills, for instance, ball mills [58], beater mills [59,60], and hammer mills [61]. The analysis of the results presented in Figure 2 suggests that grinding of pumice in the analyzed laboratory stirred mill (solid mass concentration: 20%, mill filling ratio: 70%) becomes inefficient after 5 min, as the further increase in grinding time results in only a small median particle size decrease and a very high rise in the energy consumption (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…The experiments conducted in a wet stirred media mill showed that increasing the grinding time decreases the median particle size of pumice with a simultaneous increase in the unit energy demand (Table 2 and Figure 2). A similar observation for the stirred ball mill was presented in the author's previous study for limestone [24] and other types of mills, for instance, ball mills [58], beater mills [59,60], and hammer mills [61]. The analysis of the results presented in Figure 2 suggests that grinding of pumice in the analyzed laboratory stirred mill (solid mass concentration: 20%, mill filling ratio: 70%) becomes inefficient after 5 min, as the further increase in grinding time results in only a small median particle size decrease and a very high rise in the energy consumption (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…The crushing effect of coal specimens under three-dimensional dynamic and static combined loading reflects the force state of coal specimens, and through the properties of fractal theory, the crushing block size distribution can be used, to evaluate the crushing effect of coal rock, and in the previous studies, the statistical function of crushing block size distribution with R–R (Rosin–Rammler) distribution and G-G-S (Gate-Gaudin-Schuhmann) distribution 43 45 has been used relatively frequently. In this paper, the G-G-S distribution function is used to fracture the coal samples into dimensions.…”
Section: Comparative Analysis Of Test Results and Simulation Resultsmentioning
confidence: 99%
“…The crushing effect of coal samples under three-dimensional dynamic and static combined loading reflects the force state of coal samples, and by the characteristics of fractal theory, the crushing block size distribution can be used to evaluate the crushing effect of coal rock, and in the previous studies, the statistical function of crushing block size distribution is relatively widely used with R-R (Rosin-Rammler) distribution and G-G-S (Gate-Gaudin-Schuhmann) distribution [42][43][44] widely used . In this paper, the G-G-S distribution function is used to fracture the coal samples into dimensions.…”
Section: Damage Patterns and Fractal Characteristicsmentioning
confidence: 99%